Monitoring Muscle Oxygen Asymmetry as a Strategy to Prevent Injuries in Footballers - Vasquez-Bonilla, Aldo A.; Brazo-Sayavera, Javier; Timón, Rafael; Olcina, Guillermo (Research quarterly for exercise and sport, 2023)
Purpose: It has been hypothesized that sports injury risk is explained by muscle metabolism. The objective was to evaluate the muscle oxygen saturation slopes (ΔSmO 2 slopes) and muscle oxygenation asymmetry (MO 2 Asy) at rest and to study their associations with injuries during the pre-season. Methods: A total of 16 male and 10 female footballers participated in this study. Injuries were diagnosed and classified by level of severity during the pre-season. The workload was also evaluated using the rate of perceived exertion × training time, from which the accumulated loads. The SmO 2 was measured at rest in the gastrocnemius muscle using the arterial occlusion method in the dominant and non-dominant legs. The repeated measures ANOVA, relative risk, and binary logistic regression were applied to assess the probability of injury with SmO 2 and workload. Results: Higher MO 2 Asy and ΔSmO 2 Slope 2 were found among footballer who suffered high-severity injuries and those who presented no injuries. In addition, an MO 2 Asy greater than 15% and an increase in accumulated load were variables that explained a greater probability of injury. Conclusion: This study presents the new concept of muscle oxygenation asymmetry in sports science and its possible application in injury prevention through the measurement of SmO 2 at rest.